Acute Infectious Morbidity in Multiple Gestation. (5th January 2015) - Dotters-Katz, Sarah K.; Patel, Emily; Grotegut, Chad A.; Heine, R. Phillips
Abstract : Objectives . Physiologic and immunologic changes in pregnancy result in increased susceptibility to infection. These shifts are more pronounced in pregnancies complicated by multiple gestation. The objective of this study was to determine the association between multiple gestation and risk of infectious morbidity. Study Design . The Nationwide Inpatient Sample for the years 2008–2010 was used to identify pregnant women during admission for delivery with International Classification of Diseases codes. Logistic regression was used to compute odds ratios and 95% confidence intervals for demographic data, preexisting medical conditions, and acute medical and infectious complications for women with multiple versus singleton gestations. Results . Among women with multiple gestation, 38.4 per 1, 000 women had an infectious complication compared to 12.8 per 1, 000 women with singletons. The most significant infectious morbidity associated with multiple gestation was intestinal infections, pyelonephritis, influenza, and pneumonia. After controlling for confounding variables, infectious complications at delivery persisted for women with multiples, though the association was dependent on mode of delivery. Conclusions . Women with multiple gestations are at increased risk for infectious morbidity identified at the time of delivery. This association was diminished among women who had a cesarean suggesting that operative delivery is not responsible for this association.